A multilevel analysis of the effects of HR diversity management on employee knowledge sharing: The case of Chinese employees - Shen, J.; Tang, N.; D'Netto, Brian (Routledge, 2014)
This study explored the effects of human resource diversity management on employee knowledge sharing and the mediating and moderating variables underlying this link, among Chinese employees. Multilevel analyses of the data from 716 respondents in 37 firms revealed that organizational-level HR diversity management practices explained significant variance in employee knowledge sharing. The relationship between HR diversity management and knowledge sharing was fully mediated by employee trust in the organization. Moreover, cooperative norms moderated the second stage of the mediation, which is the relationship between trust in the organization and knowledge sharing. The findings of this research provide important insights into the relationship between HR diversity management and employee work outcomes.